Microstructure Development of Powder-Based Cu Composite During High Shear Strain Processing - Lenka Kunčická; Josef Walek; Radim Kocich (Metals)
Commercially pure Cu features excellent electric conductivity but low mechanical properties. In order to improve the mechanical properties of Cu, strengthening elements can be added to prepare alloys or composites featuring enhanced performances. This study focuses on the detailed characterization of the microstructure of a Cu composite strengthened with Al2O3 particles during high shear strain processing. The Cu-Al2O3 mixture was prepared by powder metallurgy and directly consolidated by the intensive plastic deformation method of hot rotary swaging. Samples cut from the consolidated piece were further processed by the severe plastic deformation method of high pressure torsion (HPT). The primary aim was to investigate the effects of varying degrees of the imposed shear strain, i.e., the number of HPT revolutions, microstructure development (grain size and morphology, texture, grain misorientations, etc.) of the consolidated composite; the microstructure observations were supplemented with measurements of Vickers microhardness. The results showed that the added oxide particles effectively hindered the movement of dislocations and aggravated grain fragmentation, which also led to the relatively high presence of grain misorientations pointing to the occurrence of residual stress within the microstructure. The high shear strain imposed into (the peripheral region of) the sample subjected to four HPT revolutions imparted equiaxed ultra-fine grains and an average Vickers microhardness of more than 130 HV0.1.